آليات الاتساق في القصيدة الهائية لحافظ بن أحمد الحكمي - دقة, ابتسام; طويل, الزهرة (My University, 2023)
ّ ّ غػي اف لدانيات ّالم ّ ز تجاكرت دارسة الجسمة إلى ّالش ّ ،زّالش باعتبار ىحا الأخيخ بشية دلالية كمية فيػ مجسػعة مغ الجسل الستاخبصة في شكل متػاليات بيشيا علبقات دلالية تذكل نديجا لغػيا، كمػضػع داؽ ،خصية ّ الات مغ أبخز السفاـيع تي ّ ال عشيت بو ىحه المدانيات، فقج سعت لمكذف عغ الأنصسة ة ّ غػي تي ّالم ّ ال تجعل ّ ز كيانا ّالش قائسا بحاتو، كاىتست بسا يجعل ّ ز كحجة متشاسقة بػاسصة مجسػعة مغ الػسائل كالعشاصخ ّالش السختمفة ك ل ّ تتسث في آليات داؽ ّ الات مغ إحالة كاستبجاؿ كححؼ ك... كغيخىا، فيحه الطػاىخ المدانية تدعى بعجة ركابط نحػية كلغػية لتحقق ّ ز التحامو كتساسكو، كبخزت آليات ّلمش داؽ في القريجة اليائية بكل أنػاعيا عمى اختلبؼ ندبة كركد كل مشيا، كاستصعشا مغ ّالات خلبؿ استخاخج كل آلية كتحميميا ك ّ كيف ساىست في اتداؽ اليائية، ككيف ثع بط ّ الخ بيغ بيغ الأجادء السكػنة لمقريجة مسا حقق ليا استساخريتيا لالي ّ الج ة كمغ خلبليا بمػرة مػضػع القريجة العاـ، كسا تػصمشا بأف د ّ الات اؽ ليذ مجخد تتابع جسل ك إنسا ىػ تاخبط دلالي أيزا. ّ ّ الكمساتّالسفتاحية: اخبط – داؽّالات ّ ة – الت ّ الاستساخري لالي ّ حافع الحكسي. It was known in linguistic studies that the linguistics of the text contiguous the study of the sentence to the text, considering the latter a total semantic structure, as it is a group of interconnected sentences in the form of linear sequences, including semantic relations that form a linguistic fabric, and the issue of consistency is one of the most prominent concepts that these linguistics meant, it sought to reveal About the linguistic systems that make the text a self-contained entity, and it was concerned with what makes the text a coherent unit by means of a set of different means and elements, represented in consistency mechanisms such as referral, substitution, deletion, and...etc. The mechanisms of coherence in the divine poem of all kinds, regardless of the percentage of each of them, and we were able, through extracting and analyzing each mechanism, and how it contributed to the consistency of the poem, and then how to link between the constituent parts of the poem, which achieved its semantic continuity and through which the crystallization of the general theme of the poem, as we found Coherence is not just a sequence of sentences, but a semantic coherence as well.
لسانيات عامة
Keywords: Consistency - coherence - semantic continuity - Hafez Al-Hakami.